Pemetaan penelitian komunikasi terapeutik di Indonesia melalui analisis Bibliometrik berbasis aplikasi VOSviewer - Lisnarini, Naurah; Rahman, Azizul; Gobel, Sry Ade Muhtya; Saputra, Dandi (Faculty of Communication, Padjadjaran University, 2025)
Therapeutic communication plays a crucial role in supporting the healing process and improving individual health, including mental health, education, and social interaction. It aims not only to exchange information but also to build empathetic relationships between healthcare providers and patients, creating a conducive environment for healing. This study maps research trends related to